Robust autopilot of the pitch channel of unmanned aircraft vehicles - Yu. V. Gridnev; A. G. Ivanov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Automatic pitch control system of unmanned aircraft vehicles (UAVs) with different aerodynamic configuration and airframe construction is reflected here. Robust autopilot scheme is proposed for such control system. While adjusting the parameters of UAV’s control channel, robust autopilot scheme allows presetting autopilot the way the dynamic and transient errors of control system stay invariant under UAV changing. Computer modeling of robust autopilot confirms theory of the robust systems.